Efeito alelopático de extrato aquoso de folhas de Azadirachta indica A. Juss. em alface, soja, milho, feijão e picão-preto - Rickli, Helena Cristina (2011)
The family Meliaceae has been identified as one of the most promising for biological control, as most species have biologically active compounds. Among the species, the Neem (Azadirachta indica A. Juss) is that stands out most for its efficiency and low toxicity, and it is utilized to control insects, fungi and nematodes. The aim of this work was to verify the allelopathic potential of aqueous extract of fresh leaves of Neem on germination of lettuce, soybeans, maize, beans and Bidens pilosa, as a way to control this weed. The extract was obtained by grinding 200g/L of fresh leaves of the Neem (considered extract 100%) and diluting in distilled water at concentrations of 80, 60, 40, and 20%, and a control with only water. The seeds were kept in the germination chamber at a temperature of 25 degrees C, with photoperiod of 12 hours of light. The aqueous extract affected the germination percentage and average length root of lettuce, with values of 1% and 0.1, cm respectively. For the soybeans, the extract influenced negatively the average time of germination and average speed of germination. There was a drastic reduction of the average root length at higher concentration for soybean, corn and beans. For Bidens pilosa all the parameters analyzed were negatively affected, which means sensitivity to the extract. The bioassay performed in the laboratory showed that the aqueous extract of fresh leaves of Azadirachta indica has allelopathic effect on all species.